2017
DOI: 10.1002/2016jd026109
|View full text |Cite
|
Sign up to set email alerts
|

Physical controls on half‐hourly, daily, and monthly turbulent flux and energy budget over a high‐altitude small lake on the Tibetan Plateau

Abstract: Precise measurements of evaporation and understanding of the physical controls on turbulent heat flux over lakes have fundamental significance for catchment‐scale water balance analysis and local‐scale climate modeling. The observation and simulation of lake‐air turbulent flux processes have been widely carried out, but studies that examine high‐altitude lakes on the Tibetan Plateau are still rare, especially for small lakes. An eddy covariance (EC) system, together with a four‐component radiation sensor and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 43 publications
7
77
0
Order By: Relevance
“…However, the correlation coefficient for the relationship between LE and VPD on half‐hourly scale is relatively low. Similar results were obtained over a small high‐altitude lake on the Tibetan Plateau, where a weak relationship between LE and VPD on half‐hourly scale was also reported (Wang et al ., ). Other studies have found a large effect of VPD on the half‐hourly LE over lakes in Germany and Finland (Nordbo et al ., ; Goldbach and Kuttler, ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the correlation coefficient for the relationship between LE and VPD on half‐hourly scale is relatively low. Similar results were obtained over a small high‐altitude lake on the Tibetan Plateau, where a weak relationship between LE and VPD on half‐hourly scale was also reported (Wang et al ., ). Other studies have found a large effect of VPD on the half‐hourly LE over lakes in Germany and Finland (Nordbo et al ., ; Goldbach and Kuttler, ).…”
Section: Resultsmentioning
confidence: 97%
“…Wang et al . () investigated a small highland lake and found the main driver of heat flux on half‐hourly scales was wind speed, while on daily and monthly scales the water vapour and temperature gradients. A shallow subtropical lake has a small heat capacity and responds quickly to changes in atmospheric forcing, leading to a typically unstable atmospheric boundary layer (ABL) and persistently positive H and LE (Liu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the gradual development of field measurement techniques and computer performances, more observations and simulations have been conducted to study the lake properties and the lake-air interactions over the alpine and cold regions, such as over the TP (Biermann et al 2014;Gerken et al 2013;Lazhu et al 2016;Liao et al 2013;Lu et al 2017;Wang et al 2010Wang et al , 2017Zhu et al 2017). Based on the multi-source sounding data at Lake Nam Co and the MM5 model, Lv et al (2008) revealed that the variations of heat fluxes induced by the lake-land thermal contrast is an important reason for the dramatic changes of the local circulations and mesoscale weather.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, in-situ investigations have only been conducted for a few lakes in the interior TP, e.g. Nam Co (Wang et al, 2009;Zhou et al, 2013;Wang et al, 2017) and Siling Co (Guo et al, 2016;Zhou et al, 2015), which are expanding. In contrast, there have been no detailed in-situ investigations to lakes in the southern TP, where most closed lakes are shrinking.…”
Section: Introductionmentioning
confidence: 99%